The cardiothoracic ratio: a neglected preoperative risk-stratified method for patients with rheumatic heart disease undergoing valve replacement surgery. (17th July 2018) - Jiang, Lei; Chen, Wei-Guo; Geng, Qing-Shan; Du, Gang; He, Peng-Cheng; Feng, Du; Qin, Tie-He; Wei, Xue-Biao
Abstract: OBJECTIVES: It is common for patients with rheumatic heart disease to have an enlarged heart. We investigated the prognostic value of cardiothoracic ratio (CTR) in patients with rheumatic heart disease undergoing valve replacement surgery. METHODS: A total of 1772 patients were divided into 4 groups based on the quartiles of preoperative CTR: <0.56 ( n = 349), 0.56–0.61 ( n = 488), 0.61–0.66 ( n = 449) and ≥0.66 ( n = 486). The CTR was measured from postero-anterior chest radiographs. We then investigated the association between the CTR and adverse outcomes. RESULTS: In-hospital mortality was 4.0% (71/1772). Analyses of receiver operating characteristic curves showed that, at a cut-off of 0.6, the CTR exhibited 66.2% sensitivity and 64.0% specificity for detecting in-hospital death (area under curve 0.671, P < 0.001). The prevalence of in-hospital death was 7.1% in males with a CTR >0.6, which was significantly higher in males without a CTR. A similar result was observed in females (1.9 vs 5.1%, P = 0.004). Multivariable regression showed that a CTR >0.6 was an independent predictor of in-hospital (odds ratio 2.36, P = 0.005) and 1-year mortality (hazard ratio 2.06, P = 0.006). Kaplan–Meier curves, for the cumulative rate of 1-year mortality among groups, indicated that the risk of death was increased if the CTR >0.6 (log-rank 16.36, P < 0.001). CONCLUSIONS: CTR, as a simple and reproducible indicator, was identified as a prognostic factor for predicting poor outcomes in patients with rheumatic heart disease undergoing valve replacement surgery.